Meaningful measures for advanced cancer: Building a measure set to promote goal-concordant care. Issue 28 (1st October 2022) - McNiff Landrum, Kristen K.; Ross, Tom; Andiel, Corinna; Eaton, Keith D.; Edge, Stephen B.; George, Marina C.; Lakin, Joshua; Morse, Denise; Papio, Joseph; Plank, Wendy; Thacker, Lauren; Thompson, Emily; et al.
Abstract : 210 Background: Research suggests that patients with advanced cancer do not reliably receive care consistent with their goals and values, indicating an important gap. While experts promote measurement of 'goal concordant care' this construct is difficult to measure due to definitional and data complexity. The 10 cancer hospitals of the Alliance of Dedicated Cancer Centers (ADCC) have collaboratively implemented interventions to improve goal concordant care and create a wholistic measure set through the Improving Goal Concordant Care (IGCC) Initiative. Methods: ADCC launched the 3 year initiative in 2020. Oncology, palliative care and quality experts completed conceptual work prior to launch including identifying core intervention components, specific aims and potential measures. Following an environmental scan, a workgroup brainstormed relevant measures, then applied feasibility and priority ratings. Patient/family advisors provided guidance. In 2020, a measure panel initiated technical development, using existing specifications as feasible. Claims-based measures were modeled. Following alpha testing, quarterly data submission of selected measures began in 2022. Results: During the conceptual phase, the workgroup identified 60 measures. 19 measures remained following the prioritization and feasibility rating; 14 have been tested and implemented to date (Table). A stakeholder (e.g., patients, physicians, administrators) assessment regarding each measure's value in assessing quality and usefulness for improvement is in progress. Conclusions: In support of IGCC, we created a set of measures to assess progress towards achieving goal-concordant care. This measure set is intended to be useful in any cancer setting.IGCC measure set. Domain Brief Measure Title Implementation Status Training % of eligible oncologists who: · complete communications skills training · report positive perceived value of training · Quarterly submission ongoing Provider Experience % of eligible oncologists who: · report increased self-efficacy in goals of care (GOC) conversations · report distress · Implementation in Q3 2022 EHR Documentation % of patients with documentation of: · GOC discussion · palliative/supportive care referral in the last 12 months of life · hospice referral in last 6 months of life · health care proxy · Quarterly submission ongoing Utilization Among deceased patients: · total medical costs · # admissions · days admitted · days at home · location of death · Claims specification and baseline analysis complete Utilization (CMS) % of deceased patients: · chemotherapy in the last 14 days of life · ICU in the last 30 days of life · not admitted to hospice · admitted to hospice for < 3 days · Claims baseline analysis complete Outcomes % of patients who: · feel "Heard & Understood" (AAHPM) · receive care consistent with goals · Survey integration underway · Specification in process; 2023 implementation